Strategije samopomaganja za profesionalne pomagače u savjetovanju / Self-Care Strategies of Professionals in Counceling - Berc, Gordana; Šadić, Sanela; Kobić, Ozana (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
This review paper focuses on self-help strategies for helpers of different professions, but with an emphasis on counselor self-help strategies and challenges. At the very beginning of the work, the term self-care was defined and self-help strategies were explained. It is explained in the paper that self-care_a strategies include activities that achieve an optimal balance in the field of mental and physical health of helpers. For this reason, special attention was paid to the creation and maintenance of these strategies in the work. Activities in the function of self-help, in terms of their content and manner of performance as well as time commitment, have the purpose of providing the helper with relaxation, entertainment and emotional well-being. The paper describes the challenges of reconciling the business and family role of helpers as possible obstacles to maintaining a healthy boundary between work and family and an effective self-help and self-support strategy. The main postulates for reflecting the helper's self-help strategies are explained, with an emphasis on the sources of support that the work organization should provide and the activities that the helper can take personally. At the end of the paper, guidelines for the application of self-help strategies of professional helpers are described in order to encourage the improvement of regular use of effective self-help and self-support strategies.